The Development of Contextual Approach E-Modules to Improve Students’ Mathematical Problem Solving Ability on Junior High School - Komariah, Ai; Purwasih, Ratni ((JIML) JOURNAL OF INNOVATIVE MATHEMATICS LEARNING, 2024)
This study aims to develop an E-Module that can be used by teachers to support the learning process so that students more easily understand material in interactive mathematics at SMPN 4 Cipeundeuy. In order to do so, this research using research and development (Reaserch and Development) with the 4D development model (Define, Design, Develop, and Disseminate). Research conducted using this model is limited to step 3 (Define, Design, Develop) due to time and cost constraints during the research. The subjects of this study were class IX students for limited trials and class VIII students for wide trials. The data that has been collected is then analyzed using Microsoft Excel. The results of the study on the feasibility of teaching materials were seen from the results of the assessment of lesson plans, worksheets, and media with a percentage of 93.80% and the results of assessments by two mathematics teachers with a percentage of 89%. Teaching materials were tested for practicality using a student response questionnaire with a percentage of 90%. Thus this teaching material can be implemented and can be used. The results of this study can be categorized as valid, practical, and very feasible because they have received a good due diligence.